The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1111/j.1600-0773.1984.tb01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Metabolism of Sulphadiazine in Neonatal and Young Pigs

Abstract: The pharmacokinetics of sulphadiazine was studied in newborn, 1 week, and 8 weeks old piglets after intravenous administration of 60 mg/kg. Kinetic parameters were calculated using a two compartment open model. Steady state volume of distribution averaged 0.62, 0.56. and 0.48 l/kg at birth, 1 week, and 8 weeks, respectively. Elimination half-life decreased from 455 min. at birth to 322 min. at 1 week and 157 min. at 8 weeks leading to a rise in body clearance from 0.99 to 2.20 ml/min./kg during the same age pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 13 publications
(8 reference statements)
1
7
0
Order By: Relevance
“…Tissue concentrations of I4C-TMPwith the exception of the brainwere either equal to or higher than the plasma concentrations, which is in correspondence with earlier findings in adult pigs (Nielsen & Rasmussen 1975b). For a number of organs the tissue-plasma ratio was higher in the older (group B and C) than in the newborn pigs (table 3), and thus in accordance with the distribution volume of TMP being higherand above one I/kgin 1 and 8 weeks old piglets than in newborn ones (Friis et al 1984b). The higher tissue-plasma ratio in the older piglets may be explained by the observed decrease in plasma protein binding together with the postnatal reduction in extracellular fluid volume (Setiabudi et al 1975).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Tissue concentrations of I4C-TMPwith the exception of the brainwere either equal to or higher than the plasma concentrations, which is in correspondence with earlier findings in adult pigs (Nielsen & Rasmussen 1975b). For a number of organs the tissue-plasma ratio was higher in the older (group B and C) than in the newborn pigs (table 3), and thus in accordance with the distribution volume of TMP being higherand above one I/kgin 1 and 8 weeks old piglets than in newborn ones (Friis et al 1984b). The higher tissue-plasma ratio in the older piglets may be explained by the observed decrease in plasma protein binding together with the postnatal reduction in extracellular fluid volume (Setiabudi et al 1975).…”
Section: Discussionsupporting
confidence: 70%
“…The observed fall in protein binding of TMP may contribute to the simultaneous increase in the volume of distribution for TMPfrom 0.78 to 1.32 I/kg b.wt. ~ seen in piglets during the first week of life (Friis et al 1984b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, however, less information is available on the metabolism of TMP in pig. Previous studies showed that the main metabolic pathway for TMP in pig is O ‐demethylation with subsequent conjugation (Friis et al ., ; Mengelers et al ., ). Sulfation and extensive glucuronidation of 3′‐OH‐TMP and 4′‐OH‐TMP metabolites were detected in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…However, this may be due in part to the rapid body weight gain in weanling pigs that results in an effective lower amount of drug per body weight during the withdrawal period. Another option that should be explored further is that younger pigs may have metabolic differences in the liver or with drug partitioning throughout the body (Friis et al, 1984). Sulfamethazine appears to require a longer withdrawal time than the currently acceptable US withdrawal time of 15 days using the US FDA tolerance method (Table 3).…”
Section: Resultsmentioning
confidence: 96%